Sistem Pembukaan Kunci Otomatis Menggunakan Identifikasi Pola Ketukan - Alan Prasetyo Rantelino; R. Rizal Isnanto; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
During this time automatic unlocking still use the physical tools as the authentication method, which potentially damaged or lost. Authentication method of automatic unlocking system does not use technology which allows unique information to be stored without the need for physical tools and where everyone can use it. Therefore, research needs to be done to develop an automatic unlocking system using knocking pattern identification as the authentication method. System consists of hardware and software. Hardware consist of sensor which are buzzer, ATTiny85 as microcontroller and solenoid lock as actuator. Software is coded using C language with Arduino IDE which is compatible with AVR microcontroler. The system can read the knocking pattern from buzzer then identify it as true or false knock. From the test results, system can identify knocking pattern based on number of knocks, time beetween knocks and soft or loud of knocks. The system identifies the knocking patterns by analyzing its pattern compared with the true knock saved in system memory. Knocking pattern identification can be an alternative of authentication system for automatic unlocking system.